Cancer testis antigens: A new paradigm for cancer therapy - Suri, Anil (Landes Bioscience, 2012)
Cancer immunotherapy is a promising field with limited success, also due to lack of tumor-specific targets. In our attempt of exploring novel biomarkers and immunotherapeutic targets against cancer, we have discovered a novel cancer testis antigen, SPAG9, in cancers of different histological origin and demonstrated its potential role in oncogenesis.